The Role of Self-Compassion as a Mediator in the Relationship between Academic Stress and Psychological Well-Being Study on Senior High School Students - Edlyn, Jovita; Sahrani, Riana; Hendra Heng, Pamela (Eduvest - Journal of Universal Studies, 2025)
Psychological well-being is a complex construct involving optimal psychological functioning and experience. When people are experiencing problems in psychological well-being, self-compassion is a powerful resource for dealing with stress, depression, and increasing resilience. Self-compassion is directly related to feelings of compassion and concern for others. Self-compassion is very important for adolescents because adolescence is a vulnerable period for self-criticism. Education is one of the important things in the life of every human being and is an obligation for every human being. Through education, a person can develop their potential. In education, of course, there is stress in itself. Academic stress results from stress related to grades and competition for higher education advancement. The researcher conducted this study to determine whether self-compassion mediates the relationship between academic stress and psychological well-being in high school and vocational high school students. Researchers used the Hayes mediation regression analysis technique with Process to see the role of self-compassion as a mediator in the relationship between academic stress and psychological well-being of SMA and SMK students. There were 164 participants in this study, aged 15-19 years, who were high school or vocational high school students. The study results show that self-compassion fully mediates the relationship between academic stress and psychological well-being in SMA and SMK students. These results are expected to be the basis for creating intervention programs that can prevent the impact of academic stress on high school and vocational students so that they can have good psychological well-being.